Why in the Netherlands the subject of soft drugs is not controversial? Historical and social conditions of the Dutch society and their influence on law - Nazimek, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The legal situation of the Netherlands plays an invaluable role in the dispute over the legalization of soft drugs. However, this issue, despite the original regulation, is no longer a controversial topic. This is due to the interesting conditions in the Dutch society and important historical factors. The article presents an analysis of the specific elements influencing the shape of the regulation of a drug policy. Its aim is to show how important for the law effectiveness is to include such conditions into a legislative process.